Research-informed fictional histories: Dramatizing the stories of marginalised women - Wales, Prue; Sallis, Richard (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2025)
This article documents the work of two Research-based Theatre practitioners. The two case studies featured were written in different cultures, for different purposes and audiences. However, both share some common elements. They feature marginalized and largely forgotten women. One tells of the plight of foreign domestic helpers in Singapore and East Asia. The second case documents the achievements of women painters whose contribution to the Australian en plein air movement has been undervalued. In both instances we included in our playwriting what we have come to refer to as research-informed fiction. The subject matter, the intended audience, and the real-life women on whom the plays were based necessitated including fictional elements into our respective plays.